Focal Hyperostosis on CT of Sinonasal Inverted Papilloma as a Predictor of Tumor Origin - Lee, D.K.; Chung, S.K.; Dhong, H.-J.; Kim, H.Y.; Kim, H.-J.; Bok, K.H. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: To evaluate the CT characteristics of focal hyperostosis in patients with sinonasal inverted papilloma and to correlate these characteristics with the detection of the origins of tumors.MATERIALS AND METHODS: Paranasal sinus and nasal cavity CT images of 76 patients were reviewed retrospectively to detect areas within which there was focal hyperostosis. We correlated the sites on the CT scans within which there was focal hyperostosis with the origin of the tumors described in the corresponding patient’s medical records. We also evaluated the CT features of focal hyperostosis according to the origin of tumors.RESULT: Surgical evaluation of 55 lesions with focal hyperostosis in CT images revealed that 49 of these lesions coincided with the actual origin of tumor. The CT-based determination of the locations of the areas of focal hyperostosis corresponded to the actual tumor origin in 89.1% of cases. Especially in cases with focal hyperostosis within the frontal, maxillary, sphenoid, and posterior ethmoid sinuses, areas of focal hyperostosis corresponded to the origin of tumor without exception. In the evaluation of the CT features of focal hyperostosis, 2 patterns of localized bone thickening were noted. Plaquelike bone thickening was seen mainly when focal hyperostosis involved the lateral wall of the nasal cavity. On the other hand, cone-shaped bone thickening was seen only in the walls of the paranasal sinuses or the bony septum.CONCLUSIONS: A high correlation between the origin of the inverted papilloma and focal hyperostosis on CT might facilitate preoperative prediction of tumor origin by radiologists and rhinologists.